Characterization and Physical Properties of PolyvinylChloride/Silica Nanocomposite Films - Mohammad, Maryam Hussein; Saeed, Asrar Abdulmunem (Al-Mustansiriyah Journal of Science, 2023)
Using polyvinyl chloride (PVC) and SiO2 NPs in Tetrahydrofuran (THF). The casting method produced thin films of (PVC) with various amounts of SiO2 nanoparticles (0.001, 0.002, 0.003, 0.004, and 0.005) g. XRD results showed that the PVC films and SiO2 NPs had an amorphous structure. The FESEM of PVC/SiO2 nanocomposite film shows excellent SiO2 dispersion on the PVC film surface. The FTIR spectrum indicated that SiO2 NPs did not influence polymer structure. UV-Vis spectroscopy has been used to study the effects of SiO2 NPs on PVC optical characteristics, including absorption spectrum, transmission spectrum, energy band gap, absorption coefficient, extinction coefficient, refractive index, and real and imaginary dielectric constants. It was found that with increasing SiO2 NPs amount, the optical energy gap of PVC/SiO2 nanocomposite films was reduced from 4.36 to 3.39 eV. The study shows that an increase in SiO2 NPs results in a change in all of these parameters.